ETHNOPEDAGOGY-BASED LITERACY E-MODULE ON INDONESIAN LEARNING SUBJECT - Sri Rochmayanti; Galih Istiningsih (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2023)
This paper discusses a product of an Ethnopedagogy-based literacy e-module on Indonesian learning subjects for grade IV text material. The research is the ADDIE model development research, which consists of five stages, analysis, design, planning, implementation, and evaluation. The research subjects involved linguists, materials experts, culture experts, design experts and media experts, and teacher and student trials. The object of the research is an Ethnopedagogy-based literacy e-module for grade IV SD students on Indonesian learning subjects. Data collection used questionnaires, observations, and interviews through the validity of the learning media questionnaire instrument. Data were analyzed using quantitative descriptive and qualitative descriptive analysis methods. The results indicate that the product validation test based on the subject matter expert test percentage was 97.00%, the learning culture expert test was 98.00%, the learning media expert test was 92.56%, the design expert test was 98.76%, and the language expert test was 96.00%. The teacher trial was 97.25%, the individual trial was 94.25%, and the small group trial was 90.00%. It can be concluded that pedagogy-based literacy e-modules are feasible and practical to use as teaching materials for story text material in Indonesian language learning subject content for grade IV SD and can be used as a medium for literacy and introduction to local culture.